The HEXACO, academic motivation and learning approaches: evidence from a central Asian country. Issue 6 (1st July 2021) - Mahmood, Monowar; Frolova, Yuliya; Gupta, Bhumika
Abstract : Purpose: Personality traits are assumed to influence cognitive processes as well as academic motivation and learning approaches of the students. Based on these assumptions, the present study investigates the association of HEXACO personality traits with academic motivation as well as influence of those traits on students' learning approaches in educational contexts. Design/methodology/approach: Self-reported measures of personality orientation, academic motivation and learning approaches were obtained from 404 respondents in a classroom environment. The SPSS 20 software was used to conduct the correlations and the hierarchical regression analyses. The Eviews 10 software was used to develop the structural equation model to find the inter-relations among the study variables. Findings: The findings reveal the influence of personality traits on academic motivation and learning approaches of the students. Among different personality traits, consciousness appeared to have highly positive impact on deep learning and intrinsic motivation of the studies. Neuroticism appeared to have most negative impact related to surface learning and amotivation of the learning contents. Research limitations/implications: The findings validates the existence of HEXACO personality traits among the students in central Asian context. It future reiterated individual differences in learning strategies and learning motivation among the learners. The results may help academics and policy makers take appropriate measures to increase academic motivation and select appropriate learning approaches. Originality/value: This is one of the pioneer studies to investigate the relationship between HEXACO personality traits, learning strategies and academic motivation. Validation of the HEXACO framework will help to understand students' personality in a more detailed and elaborative way and will contribute to the existing literature on personality and learning outcomes.